نیند اور صحت کا باہمی تعلق- عصری تحدیات و تدارک (اسلامی تعلیمات اور عصری تحقیقات کی روشنی میں): Association between health and sleep: contemporary challenges and solution (Islamic and modern perspectives) - Dr. Hafsa Nasreen (Al Manhal Research Journal, 2024)
Sleep is a blessing Allah SWT has bestowed on mankind. It is a core pillar of health. Allah Almighty says “And made your sleep a means of repose”. Modern science and medicine has demonstrated that sleep has essential physiological functions for a healthy body and mind. And sleep deprivation has deleterious effects on various body functions, and leads to innumerable physical and mental ailments throughout our lifetime, like heart conditions, diabetes, chronic diseases, stress, depression, memory loss, loss of control over emotions etc. So sleep is essential for survival of humankind like food. But Qur’an emphasized the importance of getting sleep enough at night 1400 years ago. Prophet Muhammad SAW also stressed the point as he ordered one of his companions who was praying the whole night to “offer prayer and sleep at night as your body has a right on you”. Another hadith says “If anyone of you feels drowsy while praying he should go to bed until his slumber is over”. So sleep is very important for us. This paper deals with the role of sleep for mental and physical health in the light of Islam and modern science.